Early plasma increase in creatinine following significant kidney hypoperfusion - Md Ralib, Azrina; Pickering, John W.; Thann, Martin; Endre, Zoltan H. (2012)
Background: The limitation of plasma creatinine in AKI diagnosis is mainly due to its delayed increase from time of insult, and hence resulted in delayed diagnosis. Earlier diagnosis is made possible with the discovery of various new AKI biomarker of injury. However, their performance in heterogenous ICU population is influenced by the time of measurement from time of insult. We aimed to investigate this by measuring these biomarkers near to the time of insult, in the emergency department (ED), and during the first week of ICU and hospital stay in 3 patient groups identified as high risk for AKI.